Online Affirmation and Peer Support are Effective for Reducing Medical Personnel Stress in Dealing with Covid-19 Patients - Saleha, Nurmukaromatis; Delfina, Rina; Nurlaili, Nurlaili; Ardiansyah, Fourni; Nafratilova, Mercy (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
The Covid-19 outbreak has psychological impacts on frontline medical personnel at risk of infection. Therefore, this study aimed to evaluate the effect of online affirmations and peer support on medical personnel stress level in dealing with Covid-19 patients, as well as social support and spiritual intelligence's influence. It was a quasi-experiment with pre- and post-test administered to 25 and 30 medical personnel as the intervention and control groups, respectively. The intervention was carried out on WhatsApp group for 4 weeks. The stress level pair T-test results showed p = 0.000 in the intervention group and p = 0.238 in the control, while the independent T-test results showed p = 0.009. Social support did not affect medical personnel’s stress (p=0.978), but the effect of spiritual intelligence was significant (p=0.000). According to the results of multiple regression test conducted using the Enter method, the coefficient value (R2) = 0.584. This intervention was effective in helping medical personnel to manage stress. Hence, hospital managers need to carry out stress management training to maintain medical personnel’s mental health.